Improvement of Library Services through Friends of the Ambassador Mier - Sonah Sonah; Nurdyansyah Nurdyansyah; Siti Ruchana (Proceedings of The ICECRS, 2020)
The improvement of elementary school library services is very important especially to increase interest in reading, the limited availability of elementary school librarians has an impact on the need for cooperation to improve library services with mier ambassador friends namely library staff partners from the elements of students who have a hobby of reading. The purpose of this collaboration is to optimize the potential of school library services. Forms of cooperation undertaken include to improve the implementation of library activities programs, library promotion, reading habits habituation, reaward reading and fostering collection. This descriptive study uses a qualitative approach. The observation guide was made as a research instrument to collect data relating to the effectiveness of the collaboration of library staff and friends of Ambassador Ambassador to the increased interest in reading readers. The results of this study indicate that the library of SD Muhammadiyah 3 IKROM Wage really needs to collaborate with friends of Ambassador Ambassador to improve school library services